Coordinative-to-covalent transformation, isomerization dynamics, and logic gate application of dithienylethene based photochromic cages. Issue 33 (13th August 2020) - Zhang, Jian-Hua; Wang, Hai-Ping; Zhang, Lu-Yin; Wei, Shi-Chao; Wei, Zhang-Wen; Pan, Mei; Su, Cheng-Yong
Abstract : Metal-templated component self-assembly and then demetalation affords photochromic covalent organic cages applicable for upconversion PL-color tuning for logic gates. Abstract : Photochromic coordinative cages containing dynamic CN imine bonds are assembled from a dithienylethene-based aldehyde and tris-amine precursors via metallo-component self-assembly. The resulting metal-templated cages are then reduced and demetalated into pure covalent-organic cages (COCs), which are otherwise difficult to prepare via de novo organic synthesis. Both the obtained coordinative and covalent cages can be readily interconverted between the ring-open ( o -isomer) and one-lateral ring-closed ( c -isomer) forms by UV/vis light irradiation, demonstrating distinct absorption, luminescence and photoisomerization dynamics. Specifically, the ring-closed c -COCs show a blue-shifted absorption band compared with analogous metal-templated cages, which can be applied in photoluminescence (PL) color-tuning of upconversion materials in different ways, showing potential for constructing multi-readout logic gate systems.